The Magic Wand of the Wagnerians: Musik als Ausdruck - McClatchie, Stephen (Canadian University Music Review / Revue de musique des universités canadiennes, 1993)
As is well-known, throughout most of the nineteenth century the defence of Wagner's music was not undertaken on the same grounds on which it was attacked. Critics such as Ludwig Bischoff and Eduard Hanslick attacked Wagner's music for its alleged "formlessness" and harmonic illogicalities, while Wagner's partisans countered with appeals to vaguer criteria of beauty and truthfulness, couched generally in leitmotivic terms, often focusing on the so-called "symphonic web" of Wagner's late works. One particular strategy is encapsulated by the phrase "Musik als Ausdruck," which forms the basis of a number of late nineteenth- and early twentieth-century monographs and articles about Wagner's works. Musical gestures were held to encode a particular emotional state and to reawaken that state in the listener, who would intuit the "meaning" of the gesture instinctively; within such an aesthetic, music was held to represent the essence of phenomenon, the "thing-in-itself."This article attempts to provide an account of the dual foundations of this aesthetic paradigm in philosophy and science, as manifested by Arthur Schopenhauer's Die Welt als Wille und Vorstellung and by Friedrich von Hausegger's Die Musik als Ausdruck respectively, and suggests that the resulting position – as articulated by Hans von Wolzogen and Curt Mey – is not only incompatible with but also incomparable to that of the formalists. The reconciliation of these two positions would not take place until the 1920s and 1930s with the work of Alfred Lorenz.